Modified Altissimi and Mancini technique for carpal tunnel decompression - Sigdel, A; Uprety, S; KC, Govind (Journal of Institute of Medicine Nepal, 2013)
Introduction: Carpal tunnel syndrome is the commonest compressive peripheral nerve neuropathy; open carpal tunnel decompression still remains the preferred method as a day case procedure using local anaesthesia. The local anaesthetic is commonly administered by subcutaneous infiltration alone (the Gale technique) or by infiltration of the local anaesthetic into the carpal tunnel in addition to the subcutaneous infiltration (the Altissimi and Mancini technique). The purpose of this study was to evaluate the efficacy of the modified Altissimi and Mancini technique of local anesthesia. Methods: Fourteen hands of twelve patients age ranged from 26 to 55 years, two patients with bilateral involvements were recruited. Most involved hand was operated first with the modified Altissimi and Mancini technique of local anaesthesia. Results: Intra-operative pain was evaluated using visual analog score. Patients experienced no to very little intra-operative pain VAS 0- 2. Only one patient experienced tourniquet discomfort which subsided after release. There was neither any intra-operative nor during follow up, the signs of iatrogenic median nerve injury. Conclusion: We concluded that open carpal tunnel decompression using modified Altissimi and Mancini technique under local anaesthesia and with tourniquet control is a safe, effective and acceptable novel technique. DOI: http://dx.doi.org/10.3126/joim.v34i1.9116 Journal of Institute of Medicine, April, 2012; 34:1 9-12